2021
DOI: 10.3389/fonc.2021.598594
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab in FIGO IVB Verrucous Carcinoma of the Vulva: A Case Report

Abstract: BackgroundVulvar cancer is the fourth most common gynecologic cancer, and prognosis is poor in advanced vulvar cancer patients. Treatment for advanced vulvar cancer has not been satisfactory. In this report, we firstly report a FIGO IVB vulva verrucous carcinoma patient who obtained good prognosis after systemic treatment.Case PresentationA patient was admitted to hospital due to her vulvar lesion persistent for past 14 years. The vulvar mass has widely invaded urethra, part of anus, the lower third of the vag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The patient presented wall-eyed bilateral internuclear ophthalmoplegia (WEBINO) as immune-related adverse event [13]. Pembrolizumab also showed efficacy in a patient with vulva verrucous carcinoma in neoadjuvant setting in association with chemotherapy [14]. Pembrolizumab also demonstrated good disease control in rare histologies, such as metastatic vaginal adenocarcinoma, clear cell carcinoma of the vulva, and vulvo-vaginal mucosal melanoma [15‒18].…”
Section: Discussionmentioning
confidence: 99%
“…The patient presented wall-eyed bilateral internuclear ophthalmoplegia (WEBINO) as immune-related adverse event [13]. Pembrolizumab also showed efficacy in a patient with vulva verrucous carcinoma in neoadjuvant setting in association with chemotherapy [14]. Pembrolizumab also demonstrated good disease control in rare histologies, such as metastatic vaginal adenocarcinoma, clear cell carcinoma of the vulva, and vulvo-vaginal mucosal melanoma [15‒18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the expression level of immunosuppressive genes or immune checkpoint genes (PD-1, PD-L1, etc.) is an important cause of tumor immune escape, leading to tumor progression and poor prognosis 37 - 38 . Our study showed a significant positive correlation between GLDC and immunosuppressive genes, and the GLDC-high groups had higher immune checkpoint (PD-1, PD-L1, CTLA-4) expression levels and immune exclusion scores than the GLDC-low groups.…”
Section: Discussionmentioning
confidence: 99%
“…Different mechanisms of immune evasion have been studied in penile [ 11 , 21 , 53 , 54 ] vulvar [ 14 , 18 , 20 , 55 ] and anal cancers [ 17 , 19 ], and included immune checkpoint proteins and exhausted phenotypes for infiltrating-lymphocytes, suggesting that patients with these type of tumors can benefit from anti PD-L1 therapy [ 9 , 27 , 56 , 57 , 58 , 59 ]. Currently, there are several clinical trials ongoing for the use of immune therapy targeting PD-L1 (or its receptor PD-1) as treatment for penile, vulvar or anal cancer [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Therefore, multiplexed immunofluorescence and an objective analysis of the tumor microenvironment may contribute significantly to improve the understanding of different therapeutic targets when the access to biological material is reduced or limited.…”
Section: Discussionmentioning
confidence: 99%